2005
DOI: 10.1001/archinte.165.15.1698
|View full text |Cite
|
Sign up to set email alerts
|

Granted, Undecided, Withdrawn, and Refused Requests for Euthanasia and Physician-Assisted Suicide

Abstract: The complexity of EAS decision making is reflected in the fact that besides granting and refusing a request, 3 other situations could be distinguished. The decisions physicians make, the reasons they have for their decisions, and the way they arrived at their decisions seem to be based on patient evaluations. Physicians report compliance with the official requirements for accepted practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
84
2
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(93 citation statements)
references
References 22 publications
6
84
2
1
Order By: Relevance
“…In both countries explicit requests for euthanasia were not necessarily honoured. In our study as well as in other Dutch studies the most frequent reasons given for this discrepancy were that the patient withdrew the request or died before the request was granted [21]. However, in our study we observed that in some cases the physician in whose setting the patient died was not aware of a wish, let alone a request because these were expressed to another treating physician.…”
Section: Discussioncontrasting
confidence: 42%
“…In both countries explicit requests for euthanasia were not necessarily honoured. In our study as well as in other Dutch studies the most frequent reasons given for this discrepancy were that the patient withdrew the request or died before the request was granted [21]. However, in our study we observed that in some cases the physician in whose setting the patient died was not aware of a wish, let alone a request because these were expressed to another treating physician.…”
Section: Discussioncontrasting
confidence: 42%
“…Therefore, SCEN physicians see the more complex medical situations, and in accordance with the study performed by Pasman and colleagues, 19 it seems that physicians focus more on physical suffering. However, as loss of dignity is one of the most frequently mentioned reasons for requesting euthanasia or physician-assisted suicide, 2,6 it is important that SCEN physicians not only focus on physical symptoms but also pay attention to social, existential, and psychological factors that may influence the sense of dignity.…”
Section: Discussionmentioning
confidence: 99%
“…This is probably due to the fact that empirical research has shown that loss of dignity is an important concern for patients at the end of life. [1][2][3] Dignity is important to 92% of the Dutch general public when asked what they consider as important in their dying phase. 4 In addition, loss of dignity is one of the most common reasons to formulate an advance directive 5 and one of the most frequently mentioned reasons for requesting euthanasia or physician-assisted suicide in the Netherlands.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 It is known that most requests for euthanasia do not result in their actual completion, because either the patient dies naturally, or the physician considers the request not eligible, or a request is withdrawn. 4,5 It is noteworthy that, in particular, patients with depressive symptoms and (fear of) pain may change their mind over time. 2 In 2002, euthanasia and physician-assisted suicide were legalised in the Netherlands by the passing of the Euthanasia Act.…”
Section: Introductionmentioning
confidence: 99%